PENERAPAN SIMULASI SENAM KAKI DIABATES DALAM MENCEGAH KAKI DIABETIKUM PADA IBU AISYIAH - Sumara, Retno; Winata, Septian Galuh; Rofiqi, Erfan; Anandhita, Aries Chandra; Agustin, Ratna; Mumtaz, Dzakiyatul Fahmi (BESIRU : Jurnal Pengabdian Masyarakat, 2024)
Diabetes mellitus is a chronic disease with increasing prevalence in Indonesia that is at risk of diabetic ulcer complications. This community service aims to provide education and simulation of diabetic foot exercises for the prevention of diabetic ulcers in the Aisyiah Sidoarjo Group with 30 participants. Community service is carried out using the following methods: 1) Counseling: Providing material on diabetes mellitus, complications, and the importance of diabetic foot exercises; 2) Demonstration: The community service team demonstrates the steps of diabetic foot exercises; 3) Simulation: Participants practice diabetic foot exercises with guidance from the community service team; 4) Evaluation: Assessment of participants' knowledge and skills before and after the activity. Participants were aged 40-65 years with 100% attendance. The results showed an increase in knowledge from 65% to 85% after the activity, which was achieved through comprehensive materials, questions and answers, and demonstrations. The activity succeeded in increasing participants' knowledge and skills in diabetic foot exercises. The community service activity of Education and Simulation of Diabetic Foot Exercises for the Prevention of Diabetic Ulcers in the Aisyiah Group has been successfully implemented. There was an increase in participants' knowledge and skills in performing diabetic foot exercises.